The Application of Communicative Language Teaching Method in Vocabulary Teaching - Lilik Yuliawati; Aprillia Aprillia (Loquen, 2019)
Abstract: Since young learners have special characteristics in learning a foreign language, teachers have to create an interesting method in teaching English especially vocabulary. One of the methods usually used in teaching vocabulary is Communicative Language Teaching (CLT). The objective of the research is to know how to teach vocabulary using pictures and games in the CLT method, to investigate the advantages of teaching English vocabulary through pictures and games in CLT method, as well as to investigate the problems that occurred in teaching and learning process. The method used in this study is action research with 30 participants. The researcher collected the data by having observation, conversation, and interview. In delivering materials there are three necessary elements, those are engaged, study, and activate stage. The result shows that all the students gave positive responses to the use of pictures and games in vocabulary learning. They felt that pictures and games in the CLT method could help them understand the word meaning more easily and motivate them to learn vocabulary since the classroom activities were more interesting. Besides, this method also helped the students to pronounce each word correctly. However, there are some problems, such as the students usually feel bored when they only have one discussion for a long time. When the students have never heard of the word before, the teacher must explain it to them first. Besides, the class could be crowded and noisy.